ON THE ISSUE OF THE STUDY OF AUTOBIOGRAPHICAL MEMORY - Nikishov, Sergey Nikolayevich; Osipova, Irina Stanislavovna; Pronkina, Elena Gennadyevna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The article focuses on the topical problem of the functioning of autobiographical memory, which is considered as a higher mental function. The aim of the research is to study autobiographical memory of people of different age groups using the method of free recall of events. Methods: The main parameters of the analysis are as follows: Memories peak,â€ subjective importance of the events and dynamics of autobiographical memory. Results: The research results suggest that positive experiences dominate in the structure of autobiographical memory. This may indicate psychological protective mechanisms of a person. The dynamics of autobiographical memory is observed in all age groups. This results in changing the evaluation of events. This can be explained by a change in personality, the transformation of values, interests and moral principles of a person. Conclusion: The study revealed that subjects of all age groups primarily remember old events and, last of all, the events of the recent past.